1997
DOI: 10.1097/00007435-199703000-00007
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Evaluation of Condoms as Barriers to a Small Virus

Abstract: Few condoms allowed any virus penetration. The median amount of penetration for latex condoms when extrapolated to expected actual use conditions was 1 x 10(-5) ml (volume of semen). Thus, even for the few condoms that do allow virus penetration, the typical level of exposure to semen would be several orders of magnitude lower than for no condom at all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 9 publications
0
25
0
1
Order By: Relevance
“…Intact latex and polyurethrane condoms have been shown in vitro to be impenetrable to particles the size of sexually transmitted pathogens (Lyle et al 1997). When male condoms are used consistently, their effectiveness in reducing HIV transmission can be as high as 95% (Pinkerton et al 1997).…”
Section: Condomsmentioning
confidence: 99%
“…Intact latex and polyurethrane condoms have been shown in vitro to be impenetrable to particles the size of sexually transmitted pathogens (Lyle et al 1997). When male condoms are used consistently, their effectiveness in reducing HIV transmission can be as high as 95% (Pinkerton et al 1997).…”
Section: Condomsmentioning
confidence: 99%
“…No studies exist on their permeability to STI pathogens, although it is likely that they are at least as impermeable as condoms, which are also made of latex but thinner. Condoms have been tested in vitro for permeability to Chlamydia trachomatis, viruses and virus-sized particles [20][21][22][23][24] and except for one large study of aged condoms, 25 dams. If a piece tears during use it can easily be replaced.…”
Section: Evidence For the Effectiveness Of Dams In Preventing Hiv Tramentioning
confidence: 99%
“…One concern relates to the efficacy of inconsistent condom use on HIV prevalence. Several studies have shown that condoms significantly reduce the risk of transmission of HIV per coital act (Carey et al, 1992;Lytle et al, 1997). Logic dictates that inconsistent condom use should provide a partial protective effect intermediate between consistent condom use and no condom use.…”
Section: Inconsistent Condom Use Poor Condom Efficacy and Further Cmentioning
confidence: 99%